Pigmentos naturais: colorindo as ciências ambientais - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
The importance of pigments to humanity is evident and well documented. Although this theme is as old as the emergence of man in prehistory, currently the growing ecological awareness is seeking to reuse natural raw materials such as pigments, in order to reduce environmental impacts. In this context, considering that the natural elements in addition to the benefits to the environment and health are potential allies to the interdisciplinary process, this research had as main objective to build a didactic material of interdisciplinary practices for the contextualized teaching of Environmental Sciences with the theme of natural pigments. For this, a survey was carried out identifying known or potential sources and the description of the chemical processes of natural pigments. Data collection was carried out with ten professors/researchers from Federal Institutes and Universities who were already developing content on the subject or some practical activity with natural pigments. Due to the restrictions imposed by the COVID-19 pandemic, online forms were used through Google forms and contact with participants through social media. As for the methodological strategies, the research showed to be predominantly qualitative, exploratory type with non-probabilistic sampling. Among the procedures, to support and achieve the proposed objectives were carried out: bibliographic, documentary and field research, using as techniques for data collection: open questionnaires, direct observation, field diary and photographic records. From the results, it was possible to elaborate the educational product "Intuitive Manual of Amazonian Pigments" with interdisciplinary practices covering information sheets from regional sources chosen for the cultural and economic importance of the Amazon region: açaí, camu-camu, buriti and Amazonian soil verticalizing the knowledge of sources for insertion in the curriculum of biology and chemistry of the 2nd year of high school, and the material can be adapted to the criteria or needs of the educator and student, reiterating that the student can be the main actor in their learning, in order to tread the path the criticality and awareness of their society, with the teacher being a mediator and facilitator in this process.
Keywords: Tintas; Pingmentos; Química - Estudo e ensino; Biologia - Estudo e ensino; CIENCIAS EXATAS E DA TERRA; CIENCIAS BIOLOGICAS; Tintas naturais; Ensino transversal; Interdisciplinaridade; Sensibilização ambiental; Solo amazônico